Fostering Reflective Skills in Audiology Practice and Education - Cokely, Carol Geltman; DePlacido, Christine G. (Seminars in Hearing, 2012)
Reflection is considered a deliberate process of learning from experience with the goal of realizing effective and rewarding patient and personal outcomes. Reflective thinking has become incorporated into clinical practice and education across health-care professions. Facilitators for development of reflection and reflective practice include appropriate timing, a supportive environment, feedback, and mentorship. This article introduces the reader to models and forms of reflection, discusses facilitators and detractors to effective reflection, and reviews critical commentary. The Reflective Journal, 4 Habits of Effective Audiologic Service, and Self Reflection of Learning are three tools that guide students or practitioners in reflective activities.
Keywords: Reflection; reflective practice; reflective journal; health professional education; clinical supervision